Magnetic-pulsed forming when direct hook-up of sheet metal to source of electrical current - Batygin, Y. V.; Gavrilova, T. V.; Shinderuk, S. O.; Kovalenko, D. A.; Батигін, Ю. В.; Гаврилова, Т. В.; Шиндерук, С. О.; Коваленко, Д. А.; Батыгин, Ю. В.; Гаврилова, Т. В.; Шиндерук, С. А.; Коваленко, Д. А. (Харківський національний автомобільно-дорожній університет, 2020)
A distinctive feature of this work is that it combines theoretical and experimental studies of electrodynamic processes in a tool for processing sheet metal materials. It was proposed to use the phenomenon of magnetic-pulse attraction when directly connecting the processed sheet metal to a source of electric current. The investigated tool was considered under conditions close to the corresponding real production operation. In earlier scientific publications, such a tool was called an instrument with "direct current flow" through the object being processed. Methodology. In this article, analytical expressions were obtained for the excited currents and forces of attraction by solving the boundary electrodynamic problem, including the integration of Maxwell's equations. Results. The advantages of the low-frequency mode with intense penetration of fields through the conducting components of the system under study are illustrated by numerical estimates, in particular, it has been found that reducing the width of the main conductor of the inductor can significantly increase the energy characteristics of the system. According to the obtained ratios for currents and forces of attraction, the corresponding characteristics were calculated and the design of the operating experimental model of the magnetic-pulse device for the attraction of sheet metal with "direct current transmission" through the treated area was designed. Originality. It is shown that the dosed magnetic-impulse force action allows to control the deformation of sheet metal in the processing zone. It has been practically proven that the proposed technique can be very effective in the design of technological equipment used in the elimination of deformations both on steel objects and on aluminum objects. Practical value. Successful practical testing of the proposed tool was carried out in conditions close to real production.
Магнітно-імпульсне оброблення під час прямого підключення листового металу до джерела електричного струму
Магнитно-импульсная обработка при прямом подключении листового металла к источнику электрического тока
Keywords: magnetic-pulsed attraction; thin-walled sheet metal; “direct passage of current”; theoretical justification; flattening automobile bodies; магнітно-імпульсне притягання; тонкостінний металевий лист; «пряме проходження струму»; теоретичне обґрунтування; рихтування автомобільних кузовів; магнитно-импульсное притяжение; тонкостенный металлический лист; «прямое прохождение тока»; теоретическое обоснование; рихтовка автомобильных кузовов; 624.318; 10.30977/AT.2219-8342.2020.47.0.58